Classroom Enters the Courtroom: Stereochemistry of SN1 and SN2 Reactions in Enantiomer Patent Litigations of the Antidepressant Escitalopram. Issue 1 (19th October 2015) - Michman, Elisheva; Agranat, Israel
Abstract: The role of elementary stereochemistry is illustrated in the patent litigations of the blockbuster antidepressant drug escitalopram oxalate. An undergraduate student of organic chemistry would recognize the stereochemical courses of theintramolecular SN 2 and SN 1 reactions of the single‐enantiomer ( S )‐diolintermediate in the synthesis of the blockbuster antidepressant drug escitalopram oxalate:retention of configuration of the chiral carbon atom under basic conditions andracemization under acidic conditions, respectively. He/she, in searching for astereoselective ring‐closure reaction of the enantiomeric diol, will think of an SN 2 reaction in a basic medium. From these points of view, the process claim in the enantiomer patents of escitalopram is obvious/lacks an inventive step. An organic chemistry examination problem based on this scenario is offered. Chirality 28:39–43, 2016 . © 2015 Wiley Periodicals, Inc. Abstract : The role of elementary stereochemistry is illustrated in patent litigations of the antidepressant escitalopram oxalate. Undergraduate organic chemistry students would recognize the stereochemical courses of intramolecular SN 2 and SN 1 reactions of the (–)–diol in the synthesis of escitalopram: retention of configuration (basic conditions), racemization (acidic conditions), respectively. They will think of an SN 2 reaction in a basic medium. From this perspective, the process claims in enantiomer patents of escitalopram is obvious. An examination problem based on this scenario is offered.